Pengaruh Pemberian Bakteri Bacillus pumilus pada kotoran Sapi Sebagai Pupuk terhadap Jumlah Kandungan Klorofil Dunaliella salina [The Effect of Bacteria Bacillus pumilus In Cow Dung As Fertilizer to Total Chlorophyll Dunaliella salina] - Endang Dewi Masithah; Nuansa Adharia Ningrum; Setiawati Sigit (Faculty of Fisheries and Marine Universitas Airlangga, 2011)
AbstractDunaliella salina is one type of natural food used in the hatchery business. Production stability D. salina with an abundance of nutrients can be supported. The purpose of this study was to determine the effect and how many doses of the bacteria Bacillus pumilus best fermented in cow dung as fertilizer in increasing the population of D. salina. Research conducted at the Laboratory of Education Faculty of Fisheries and Marine Fisheries, Airlangga University Surabaya. The research design used was Completely Randomized Design (CRD) is followed by Duncan test. D. salina was cultured in 250 mL glass bottle with 5 treatments (2 treatments as a control) and four replications. Culture medium used contained 10 ppm cow dung. The concentration of cow manure are given in the study, namely A (12.5% Bacillus pumilus), B (10% Bacillus pumilus), C (7.5% Bacillus pumilus), control 1 (without fermentation), control 2 (fertilizer Walne). The results showed that the addition of Bacillus pumilus on cow dung that were cultured in culture medium D. salina can increase the amount of chlorophyll content of D. salina. Addition of Bacillus pumilus by 10% in the culture medium to produce the amount of chlorophyll-a D. salina high of 0.014055 µg/mL and chlorophyll-b of 0.009657142 µg/mL on the first day.